2011
DOI: 10.1007/s11103-011-9774-0
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse and field cultivations of antigen-expressing potatoes focusing on the variability in plant constituents and antigen expression

Abstract: The production of plant-derived pharmaceuticals essentially requires stable concentrations of plant constituents, especially recombinant proteins; nonetheless, soil and seasonal variations might drastically interfere with this stability. In addition, variability might depend on the plant organ used for production. Therefore, we investigated the variability in plant constituents and antigen expression in potato plants under greenhouse and field growth conditions and in leaves compared to tubers. Using potatoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Finally, the variability in antigen expression could depend also on the different plant growth conditions used. For example, Mikschofsky et al [94] compared greenhouse and field production of potato-made foreign protein using potato expressing VP60 (structural capsid protein of the rabbit hemorrhagic disease virus), CTB and the marker protein NPTII and concluded that equal or higher expression levels with lower variability of foreign protein could be expected in the fields compared to greenhouse production.…”
Section: Pharmaceutical Production In Food Cropsmentioning
confidence: 99%
“…Finally, the variability in antigen expression could depend also on the different plant growth conditions used. For example, Mikschofsky et al [94] compared greenhouse and field production of potato-made foreign protein using potato expressing VP60 (structural capsid protein of the rabbit hemorrhagic disease virus), CTB and the marker protein NPTII and concluded that equal or higher expression levels with lower variability of foreign protein could be expected in the fields compared to greenhouse production.…”
Section: Pharmaceutical Production In Food Cropsmentioning
confidence: 99%
“…In plants, both secretory and chloroplast-derived CTB expression have been demonstrated [40,41]. Plant-derived fusion proteins of CTB expressing different antigens via the secretory pathway have been successfully used to induce specific immune responses and therapeutic effects [42][43][44][45][46][47][48]. No harmful effects could be detected when CTB was applied to mice [36,40,49,50].…”
Section: Case Studies For Experimental Field Releases Of Pmp and Pmi mentioning
confidence: 99%